IMPROVING LEARNING OUTCOMES ON THE CONCEPT OF SUBSTANCE FORMS AND THEIR CHANGES THROUGH THE 'FRIENDLY AND HEALTHY SOAP' EXPERIMENTAL METHOD AND ROLE PLAYING METHOD: EXPERIMENTAL STUDY ON ELEMENTARY SCHOOL STUDENTS - Yasinia, Amira Riski; Rahmawati, Ika Dian; Wulandari, Rika (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This study was motivated by the low interest and involvement of students in learning Natural Science in elementary schools, which was caused by ineffective learning methods and difficulties in understanding abstract concepts. This study aims to identify the effect of the